Effectiveness Of The Modified Al-madinah Program In Improving Self-concept And Motivation Of Gifted Students In Saudi Arabia - Nadr A, Alsharari Sultan (2021)
The main objective of the current study is to enhance self-concept and motivation of gifted students in Saudi Arabia through the evaluation of the implemented program of Al-Madinah. This is a mixed method study (quantitative and qualitative) which involved samples from the 7th, 8th, and 9th grade of school students. Eighty students were involved in the quantitative method which have been divided equally into two groups and ten students were involved in the qualitative method. One group was exposed to the Modified Al-Madinah Program and the other group was under the conventional teaching methods. The quantitative data gathered was analysed by a statistical program (SPSS), while the qualitative data was analysed with NVivo. The results revealed that motivation and self-concept have significant effect after the used of application of the program. self-concept. There was a no statistically significant difference between the two groups with respect to birth order and grade education in both constructs, while age exerted significant effect on self-concept. Finally, the students and teachers’ perspectives were positive towards the program. Also, this study evokes the educational sector to give more attention on this group of the society as they can be a great source of society wealth and its development.